Enzyme Inhibitors and Activators 2017
DOI: 10.5772/65934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Ions, Chemical Agents and Organic Compounds on Lignocellulolytic Enzymes Activities

Abstract: Lignocellulolytic enzymes have been extensively studied due to their potential for industrial applications such as food, textile, pharmaceutical, paper, and, more recently, energy. The influence of metal ions, chemical agents, and organic compounds on these enzyme activities are addressed in this chapter, based on data available in the scientific literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 128 publications
3
23
0
5
Order By: Relevance
“…When the effect of ions and other chemicals on the enzymatic activity was tested, no ion caused any significant increase in enzymatic activity and it was completely inhibited by Cu 2+ and Fe 2+ ions when using either substrate (Table 1). Different effects on beta-glucosidases have been reported for those metals, mostly decreasing the enzyme activity by several degrees (Pereira et al, 2017) supposing that at least part of the iron oxidizes to Fe 3+ , a favorable reaction. Heavy metals, such as Cu 2+ , exhibit high affinity for thiol groups; usually, these heavy metal ions oxidize the functional groups of the cysteine residues and may inhibit the enzymatic activity of certain proteins (Hayashi et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the effect of ions and other chemicals on the enzymatic activity was tested, no ion caused any significant increase in enzymatic activity and it was completely inhibited by Cu 2+ and Fe 2+ ions when using either substrate (Table 1). Different effects on beta-glucosidases have been reported for those metals, mostly decreasing the enzyme activity by several degrees (Pereira et al, 2017) supposing that at least part of the iron oxidizes to Fe 3+ , a favorable reaction. Heavy metals, such as Cu 2+ , exhibit high affinity for thiol groups; usually, these heavy metal ions oxidize the functional groups of the cysteine residues and may inhibit the enzymatic activity of certain proteins (Hayashi et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of cations and reagents in the enzyme assay on BGL50 was evaluated by measuring the enzyme activity in the presence of KCl, MgCl 2 , NaCl, MnCl 2 , FeCl 3 , CuCl 2 , CoCl 2 , NiCl, AlCl 3 , BaCl 2 , ZnCl 2 , LiCl 2 , PVA, DMSO, Triton-X-100, Isopropanol, PEG, Ethanol, Acetone, EDTA, DTT, SDS and glucose in a final concentration of 2.5 mmol L −1 . The results were compared with those of the control sample not exposed to those chemicals (with a reference of 100%) using Student's ttest for two independent samples (Zar, 2010), adopting as significant values of p < .05, performed by QtiPlot software version 0.9.9.11 (© Ion Vasilief 2004-2017.…”
Section: Enzyme Characterizationmentioning
confidence: 99%
“…On the other hand, the inhibitory effect observed experimentally by heavy metals, such as Hg 2+ and Ag 2+ , could be attributed to the formation of cysteine-conjugates with these metals that might affect neighboring residues inducing conformational changes that may lead to alterations or loss of the catalytic activity of the enzyme. (Pereira et al, 2017) (Supplementary Figure 2). This latter effect may additionally be attributed to the significant number of Trp residues of XynDZ5, where five out of twelve are located in the environment of the catalytic site, i.e.…”
Section: -80mentioning
confidence: 99%
“…W345 that is located at the active site and four additional residues W104, W140, W178, W344 in the vicinity, according to the predicted 3D structure. Previous studies showed that the indole ring of Trp may undergo oxidation in the presence of mercury and silver, inducing conformational changes that could affect substrate binding (Pereira et al, 2017;Zhang et al, 2017).…”
Section: -80mentioning
confidence: 99%
“…We find that choosing the Ala43-Gly83 region (CBHI numbering) is promising due to its closeness to the Co 2+ metal ion in the crystal structure of CBHI, which does not exist in the crystal structure of EGI [24] (see Figure S2). Among many metal ions, Co 2+ ion is reported as a cellulase activator [25].…”
Section: Construction Of Egi_swapped and Cloning Approachmentioning
confidence: 99%